2016
DOI: 10.1111/ctr.12692
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension as a risk factor of mortality after lung transplantation

Abstract: Post-capillary PH was present in 11% and pre-capillary PH in 41% of the transplant cohort. Post-capillary PH and pre-capillary PH were associated with inferior 90-d survival, but long-term survival was unaffected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…The role of PH in this context has not been completely revealed. 1,[9][10][11][12] In our study, moderate to severe PH was diagnosed by RHC in one-fifth of the study population. These data confirm that PH is a highly prevalent condition in patients with end-stage pulmonary disease.…”
Section: After the Establishment Of A Pgd Consensus Definition Inmentioning
confidence: 50%
See 4 more Smart Citations
“…The role of PH in this context has not been completely revealed. 1,[9][10][11][12] In our study, moderate to severe PH was diagnosed by RHC in one-fifth of the study population. These data confirm that PH is a highly prevalent condition in patients with end-stage pulmonary disease.…”
Section: After the Establishment Of A Pgd Consensus Definition Inmentioning
confidence: 50%
“…Andersen et al demonstrated that pre‐ and post‐capillary PH are risk factors for increased 90‐day mortality after LTX. Interestingly, the analysis did not detect any difference, in terms of long‐term survival post‐transplantation, in these patients compared to patients without PH …”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations